Homosexuality : a psychoanalytic study - Bieber, Irving (New York, N.Y. : Basic Books, 1962)
"This volume presents a systematic study of 106 male homosexuals and 100 male heterosexuals in psychoanalytic treatment with members of the Society of Medical Psychoanalysts. It is the first time that voluminous and detailed data obtained in individual psychoanalyses have been collected for such a large number of homosexuals and subjected to clinical and statistical analysis. This is also the first published study in which a group of full-time psychoanalysts have participated in such an extensive, long-term research program"--Preface. (PsycINFO Database Record (c) 2006 APA, all rights reserved)
Includes bibliography and index.